Cyprian u Tymoteusza. Odwołania do decyzji synodalnych Cypriana z Kartaginy w polemice w Kościele Orientalnym w VIII wieku - Żelazny, Jan Witold (Vox Patrum, 2019)
The analysed texts taken from Lettersof Timothy I the Patriarch of Baghdad on his dispute with Solomon, Bishop of Hedata – a dispute over recognition of baptism given in communities outside the Assyrian Church of the East (Severians and Melkites, or Monophysites and Orthodoxy followers in older terminology) – do not give the basis for claiming there was any kind of close contact between the Oriental Christians and Christians in Africa. Being aware of the controversies and struggles of Africans and the letters written in this context in Africa Proconsularis, in the Middle East and Middle Asia gives no grounds for forming categorical judgments either. A reference to specific judgments originating from Carthage is a fact. The quotes, however, may as well come from collections of legal documents consisting of the synod’s decisions (without the context of their origin). This type of collection was common at that time and we know that both adversaries had access to them. Nevertheless, one thing is certain: for both debaters, Timothy and Solomon living in Mesopotamia in the 8th century, the heritage of African Synods from the 3rdcentury is their own heritage, and the decisions taken there applied to them. Being aware of the common tradition and communication is an axiom both in the dispute and the reasoning.